Synthesis, Spectral and Thermal Studies of VO(IV) and UO2(VI) Complexes with N,N’-Triethylenediamine-bis(3-carboxypropenamide) - Viswanathan, M. (Asian Journal of Chemistry, 2016)
The complexes of VO(IV) and UO2(VI) with N,N'-triethylenediamine-bis(3-carboxypropenamide) (TEBCPH2) have been synthesized and characterized by chemical analysis, conductance, magnetic, infrared spectral and thermal studies. On the basis of the above studies it is concluded that the ligand acts as hexadentate in dioxouranium(VI) complex whereas in the oxovanadium(IV) complex the ligand shows tetradentate nature. The VO(IV) and UO2(VI) complexes have been assigned the formulae [VO(TEBCP)]·2H2O and [UO2(TEBCP)] respectively.